IMPLEMENTASI PEMBANGUNAN SKYBRIDGE DI KOTA SURAKARTA - Wahyu Nurharjadmo; Mahardhika Mulya Adi Pamungkas (Badan Perencanaan Pembangunan Daerah, Penelitian dan Pengembangan Kabupaten Sragen, 2019)
This study aims to determine the processes and factors that influence the implementation of skybridge development in Surakarta City. The research method used is descriptive qualitative. The method of data collection uses interview and documentation, the process of data validity is done by source and technique triangulation. The results of this study concluded that the process of implementing skybridge development in Surakarta City was divided into three stages, namely the stage of organizing, interpreting, and application. There are supporting factors for implementation such as the Basic Size Factors and Policy Objectives; Sources of Factors: Communication Factors in aspects of transmission, aspects of clarity, aspects of consistency, aspects of accuracy in implementers, and directly affected communities; Factors Bureaucratic structures on aspects of organizational structure, aspects of work coordination flow, and aspects of standard operating procedures; Factors of Economic, Social and Political Conditions on aspects of the general public's opinion on policy; and the Implementing Tendency Factor. In addition there are also inhibiting factors such as the Communication Factor in the aspect of accuracy in people who are not directly affected; Factors of Bureaucratic Structure on aspects of fragmentation; Factors of Economic, Social and Political Conditions on the aspects of the influence of social conditions.